Rituals of Violent Masculinity: A Feminist Comparative Historical Analysis of Male-Male Fighting, Shame and Misogyny - Batistich-Vogels, Christina (Hipatia Press, 2026)
This article uses a combination of two feminist research methods to further understanding of the enduring nature of men’s use of ritualised forms of violence. In particular, this article examines men fighting other men to mitigate the effects of feminized shame and to stabilise masculine honour. Using a feminist comparative historical analysis alongside a feminist systematic review, two manifestations of ritualised honour-based fighting will be explored: men’s duelling of the eighteenth and nineteenth century and today’s (hetero)romantic and homosocial practice of territory marking: men claiming ownership over their (hetero)romantic partner by threatening to fight other men who appear to be romantically interested in her. By looking at the relationship between two types of ritualised fighting from different time-periods, the enduring nature of why men fight other men to mitigate feminized shame can be discussed in new ways. This type of analysis helps shed light on inherent fragilities within these violent practices, signalling how men’s ritualised fighting could be destabilised in the future.
Keywords: 440507 Studies of men and masculinities; 441010 Sociology of gender; 440502 Feminist methodologies; 4303 Historical studies; 1608 Sociology; 2002 Cultural Studies; 4404 Development studies; 4405 Gender studies; 4410 Sociology; territory marking; (hetero)romantic relationships; gender hegemony; shame; ritualized violence